Synthesis, DNA-binding, and antitumor activity of polypyridyl-ruthenium(II) complexes [Ru(L)2(DClPIP)] (L = bpy, phen; DClPIP = 2-(2, 4-dichlorophenyl)-1H-imidazo[4, 5-f][1, 10]phenanthroline). Issue 12 (18th June 2019) - Guan, Shouhai; Pan, Tao; Zhang, Yanyang; Zeng, Zhaolin; Mu, Luwen; Zhu, Duo; Chang, Boyang; Zheng, Kangdi; Qian, Jiesheng; Xie, Qiang; Mei, Wenjie; Tang, Wenjie; et al.
Abstract: Two new ruthenium(II) complexes, [Ru(bpy)2 (DClPIP)](ClO4 )2 (1 ) and [Ru(phen)2 (DClPIP)](ClO4 )2 (2 ) (bpy = 2, 2′-bipyridine, phen = 1, 10-phenanthroline, and DClPIP = 2-(2, 4-dichlorophenyl)-1 H -imidazo[4, 5- f ][1, 10]phenanthroline), have been prepared in high yield by using microwave-assisted synthesis technology. The anticancer activity of the two ruthenium(II) complexes against A549, C6, CNE-1 and MDA-MB-231 cell lines has been evaluated by MTT assay and results showed that 2 exhibited higher antitumor activity than 1 toward all the selected tumor cell lines. Besides, A549 cell line was sensitive to both ruthenium(II) complexes, especially to 2 (IC50 = 8.01 ± 0.36 μM). Meanwhile, 2 showed low toxicity against MCF-10A human normal cells. Furthermore, the DNA-binding properties of the two new ruthenium(II) complexes with CT-DNA have been investigated by electronic absorption titration, luminescence spectra, circular dichroism spectra and viscosity measurements. The results suggested that 1 and 2 were able to interact with CT-DNA via intercalative mode with a strong binding affinity in the order 2  > 1 . All of these results suggested that anticancer activity of both ruthenium(II) complexes could be closely related to their interaction with DNA. Graphical Abstract: